2018
DOI: 10.1037/neu0000385
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering in healthy aging and early stage Alzheimer’s disease.

Abstract: The decreased self-reported MW in older adults and the further decline in AD are consistent with the cognitive resource account of MW. Behavioral indices suggest that AD is on a continuum with healthy aging, with the exception of posterror slowing that may suggest performance monitoring deficits in early AD individuals (e.g., lack of error awareness). (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 92 publications
(240 reference statements)
8
73
3
Order By: Relevance
“…retaining a stimuli, pressing the key) and, therefore, it might trigger less mind wandering than our scale in which patients had to reflect on their daily experiences. This said, the present findings and those of Gyurkovics et al show how mind wandering in AD can vary according to the assessment . In our view, AD patients might show increased mind wandering in everyday life and decreased mind wandering on tasks requiring sustained attention.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…retaining a stimuli, pressing the key) and, therefore, it might trigger less mind wandering than our scale in which patients had to reflect on their daily experiences. This said, the present findings and those of Gyurkovics et al show how mind wandering in AD can vary according to the assessment . In our view, AD patients might show increased mind wandering in everyday life and decreased mind wandering on tasks requiring sustained attention.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, AD patients seem to show a tendency to shift from external stimuli to task‐unrelated thoughts and concerns. The present findings can be compared with a recent study by Gyurkovics et al , who found that the frequency of mind‐wandering decreased as a function of age; the authors also observed a further decrease of mind wandering in AD patients . These conflicting findings of Gyurkovics et al and those observed in the present study can be reconciled by emphasizing a crucial difference between our procedures and those used by Gyurkovics et al In the present study, participants’ mind wandering was assessed using a scale describing everyday life situations, whereas Gyurkovics et al used a laboratory task assessing mind wandering in the “here and now” (i.e.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations